Allopatric divergence and secondary contact with gene flow: a recurring theme in rattlesnake speciation. (26th June 2019) - Schield, Drew R; Perry, Blair W; Adams, Richard H; Card, Daren C; Jezkova, Tereza; Pasquesi, Giulia I M; Nikolakis, Zachary L; Row, Kristopher; Meik, Jesse M; Smith, Cara F; Mackessy, Stephen P; Castoe, Todd A
Abstract: The study of recently diverged lineages whose geographical ranges come into contact can provide insight into the early stages of speciation and the potential roles of reproductive isolation in generating and maintaining species. Such insight can also be important for understanding the strategies and challenges for delimiting species within recently diverged species complexes. Here, we use mitochondrial and nuclear genetic data to study population structure, gene flow and demographic history across a geographically widespread rattlesnake clade, the western rattlesnake species complex ( Crotalus cerberus, Crotalus viridis, Crotalus oreganus and relatives), which contains multiple lineages with ranges that overlap geographically or contact one another. We find evidence that the evolutionary history of this group does not conform to a bifurcating tree model and that pervasive gene flow has broadly influenced patterns of present-day genetic diversity. Our results suggest that lineage diversity has been shaped largely by drift and divergent selection in isolation, followed by secondary contact, in which reproductive isolating mechanisms appear weak and insufficient to prevent introgression, even between anciently diverged lineages. The complexity of divergence and secondary contact with gene flow among lineages also provides new context for why delimiting species within this complex has been difficult and contentious historically.